Planar versus triptycenylene end-capped aroyleneimidazoles as electron acceptors in organic photovoltaics - Menke, Elisabeth H.; Leibold, David; Galow, Alexander P.; Vaynzof, Yana; Mastalerz, Michael (Organic chemistry frontiers, 2017)
The effect of triptycenylene end-groups on the optoelectronic properties of aroyleneimidazoles and their performance as acceptors in bulk heterojunction photovoltaic devices are described. We compare three derivatives of triptycene monoaroyleneimidazoles with their planar analogues. Planar aroyleneimidazoles show rather poor performance as acceptors with power conversion efficiencies (PCEs) of ∼0.3-1.3%. In contrast, the triptycene end-capped congeners show improved performance with a maximum PCE of 2.3%, demonstrating the potential of triptycene-based π-systems for application as non-fullerene electron acceptors.
Gesehen am 26.09.2018